غريب القرآن الكريم وصف وتحليل - ربة, امحمد (جامعة الوادي university of eloued, 2023)
من المتفق عليه أن شرف العلم من شرف المعلوم به، ومما لا ريب فيه أن الاشتغال بكلام الله عز وجل من أنفع المعارف وأسمى الغايات، ومن هذا المنطلق سَعَت هذه الورقة البحثية وأَبَت إلا أن تسْتثير علما مهمّا وشريفا من علوم الكتاب العزيز؛ وهو علم الغريب، الذي صار كاسمه تماما بين الأنام، حيث عزّ فيه البحث وقلَّت إثارة مسائله بين كثير من الباحثين، وإن كانوا من المشتغلين في حقل الدراسات القرآنية واللغوية سيما المعاصرون منهم؛ حتى صار غريبا في كتاباتهم العلمية وبحوثهم، ولهذه الدواعي قد تم في هذه الورقة العلمية: الإبانة عن هذه الظاهرة اللفظية، وذلك من جهة: بيان مفهومها لغة واصطلاحا، وإبداء مدى أهميتها الكبرى في توجيه دلالات النصوص القرآنية، وكذا إماطة اللثام عن مصدرها الذي تُستقى منه وتـَحتكِم إليه؛ وهو لسان العرب، لأخُلُص في ختام البحث إلى ثبوت فضيلة علم الغريب ودوره الأساس في تقريب معاني كلام الرحمن إلى قلوب الأنام. Knowledge honour is a part of the known honour, and with no doubt, dealing with Quran is a paramount objective and a beneficial knowledge. From this basis, this research paper looks for raising one of Quran sciences, which is the science of ambiguous words in Quran, that becomes weird among people. Research in this science is decreased, and its issues are rarely addressed among many researchers, although they deal with Quran Linguistic Studies field, especially the modern ones, so it becomes absent in their scientific writings. Therefore, this paper demonstrates this uttered phenomenon in terms of: illustrating its concept linguistically and terminologically, its importance in guiding Quranic texts significances, and clarifying its source, which is the Arab language. The research paper has concluded with the fact that this science is so important, and its main role is to interpret Quran ambiguous words to people
مقال
Keywords: القرآن الكريم، جلاء، الأذهان، الغريب.